Improvement of clayey subgrades through the addition of steel waste (2020)
This work evaluates the behaviour of clay soil mixture by adding stell waste/slag, comparering with the quality criteria to be a subgrade road. The behavior of the mixture of steel waste with kaolinite clay was established with a dosage matrix of global increase, in percentages of 25, 50 and 75% through sieve number 4. The results show that the steel waste works on cohesive materials, reducing plasticity by up to 0%, and increasing the California Bearing Ratio (CBR) value, by 378.92%. It is possible to conclude that the steel waste is an excellent complement for improving the physical and mechanical properties of kaolinite clay subgrade. In a first approximation, the most recommended dosage is 25%, because the reduction of resistance to compression and plasticity index was not as high as in other dosages, but it increases the CBR index and the density.